Technological change : (Methuen, 1970)
The technological and industrial history of the United States describes the United States' emergence as one of the most technologically advanced nations in the world. The availability of land and literate labor, the absence of a landed aristocracy, the prestige of entrepreneurship, the diversity of climate and a large easily accessed upscale and literate free market all contributed to America's rapid industrialisation. The availability of capital, development by the free market of navigable rivers, and coastal waterways, and the abundance of natural resources facilitated the cheap extraction of energy all contributed to America's rapid industrialization.